Complementary and Alternative Medicine: Are Medical Students in AlKhobar, Saudi Arabia Interested? - Alamoudi, Naela B.; Itani, Sarah A.; Shafey, Marwa M.; Abdel Wahab, Moataza M. (International Journal of Innovative Research in Medical Science, 2020)
This study aimed to assess the knowledge and attitude of medical students toward complementary and alternative medicine. A cross-sectional design was used, in which a total of 319 fourth- to sixth-year medical students at a local university hospital participated in self-administered questionnaires during the academic year of 2018-2019. The questionnaire assessed levels of perceived knowledge, attitude, and willingness to recommend complementary and alternative therapies. It showed that most students (95.6%) have heard of complementary and alternative medicine previously, and 74.6% of students held a positive attitude toward it. The majority had perceived knowledge about nutritional supplements (63.2%), prayer (60.9%), and yoga/meditation (60.9%), but less than 50% had perceived knowledge about other common therapies. Only 8.7% of the participants thought that their current knowledge about complementary and alternative medicine is adequate. Students were willing to recommend therapies that they were most familiar with, namely prayer (82%), massage (74%), and yoga/meditation (72.6%). Most students (60.5%) got their information about complementary and alternative medicine from the university curriculum. Yet, they did not believe that it provided them with adequate information. In conclusion, medical students showed a positive attitude toward complementary and alternative medicine despite their limited perceived knowledge. We recommend incorporating a complementary and alternative medicine course in the medical curricula that focuses on common therapies in Saudi Arabia.